PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI 2 KETOL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN MENGGUNAKAN MEDIA PUZZLE HURUF - Putri Handayani; Alfi Syahrin; Muhammad Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Beginning reading is a fundamental literacy skill that elementary school students must acquire, as it provides the foundation for learning across all subject areas. Based on the findings of a preliminary observation conducted in Grade I of SD Negeri 2 Ketol, students' beginning reading skills were found to be relatively low. Of the 23 students, only 12 (52.17%) achieved the Minimum Learning Mastery Criterion (KKTP) of 75 or above. This study aimed to improve students' beginning reading skills through the implementation of the Think–Pair–Share (TPS) cooperative learning model supported by letter Puzzle media. In addition, the study sought to describe teacher and student learning activities as well as students' responses to the instructional process. The study employed a qualitative approach using Classroom Action Research (CAR), which was conducted over two cycles. The participants consisted of 23 first-grade students of SD Negeri 2 Ketol during the 2025/2026 academic year. Each cycle comprised four stages: planning, action, observation, and reflection. Data were collected through reading achievement tests, classroom observations, and interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data from interviews were analyzed following the interactive model of Miles and Huberman. The findings revealed that the implementation of the Think–Pair–Share (TPS) cooperative learning model supported by letter Puzzle media effectively improved students' beginning reading skills. The percentage of students achieving mastery increased from 52.17% in the pre-cycle to 60.86% in Cycle I and further to 86.96% in Cycle II. Teacher activity improved from 77.71% to 97.14%, while student activity increased from 75.14% to 100%. Furthermore, students expressed highly positive responses to the learning activities, reporting that the instructional approach was more engaging, enjoyable, and helpful in recognizing letters and reading simple words. These findings indicate that the implementation of the Think–Pair–Share (TPS) cooperative learning model supported by letter Puzzle media is effective in enhancing the beginning reading skills of first-grade students at SD Negeri 2 Ketol.